O financiamento do desenvolvimento sustentável: Um panorama da evoluç\~ao dos títulos temáticos - Carlos Eduardo Lampert Costa (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The phenomenon of climate change, which has been guiding discussions around the contemporary economic development process, has sparked a series of initiatives aimed at outlining strategies for the future of humanity. Considering the magnitude of the challenge to be faced, which involves a profound transformation of the current development model, the estimated need for financial resources reaches considerable values. The so-called "market for sustainable financial products," a segment that involves a range of instruments backed by debt assets, has shown significant performance in recent years as a source of financing to tackle the challenges posed by the impacts of climate change. In this context, the objective of this study is to analyze the evolution of the issuance of so-called thematic bonds as a mechanism of supplementary financing to the transition process through which the global economy is undergoing.
Keywords: G12; H81; Q51; Q54; 330; sustainable development financing; energy transition; sustainable debt market; thematic bonds; green bonds